Sintering‐induced delamination of thermal barrier coatings by gradient thermal cyclic test - Cheng, Bo; Zhang, Yu‐Ming; Yang, Ning; Zhang, Meng; Chen, Lin; Yang, Guan‐Jun; Li, Cheng‐Xin; Li, Chang‐Jiu (Journal of the American Ceramic Society, 2017)
Lifetime is crucial to the application of advanced thermal barrier coatings (TBCs), and proper lifetime evaluation methods should be developed to predict the service lifetime of TBCs precisely and efficiently. In this study, plasma‐sprayed YSZ TBCs were subjected to gradient thermal cyclic tests under different surface temperatures, with the aim of elucidating the correlation between the coating surface temperature and the thermal cyclic lifetime. Results showed that the thermal cyclic lifetime of TBCs decreased with the increasing of surface temperatures. However, the failure modes of these TBCs subjected to thermal cyclic tests were irrespective of different surface/BC temperatures, that is, sintering‐induced delamination of the top coat. The thickness of thermally grown oxide (TGO) was significantly less than the critical TGO thickness to result in the failure of TBCs through the delamination of top coat. There was no phase transformation of the top coat after failure. In contrast, in the case concerning the top coat surface of the failure specimens, the elastic modulus and microhardness increased to a comparable level due to sintering despite of the various thermal cyclic conditions. Consequently, it is conclusive that the failure of TBCs subjected to gradient thermal cyclic test was primarily induced by sintering during high‐temperature exposure. A delamination model with multilayer splats was developed to assist in understanding the failure mechanism of TBCs through sintering‐induced delamination of the top coat. Based on the above‐described results, this study should aid in facilitating the lifetime evaluation of the TBCs, which are on active service at relatively lower temperatures, by an accelerated thermal cyclic test at higher temperatures in laboratory conditions.